Determinan Opini Audit Going Concern pada Perusahaan Sub Sektor Hotel dan Pariwisata - Prasetyo Ramadhan; Ali Fikri; Yura Prayoga (Akuntabilitas, 2022)
This study aims to analyze the determinants of going concern audit opinions on hospitality and tourism companies listed on the Indonesia Stock Exchange. The type of data used in this study is secondary data obtained from the company’s website or the Indonesia Stock Exchange website. The sampling technique in this article uses purposive sampling and gets 44 samples. The data analysis method used in this study is Panel Data Regression using the Random Effect model and the results show that only the leverage ratio has an effect on going concern audit opinion. While other variables such as financial distress, liquidity ratio, company size and profitability ratios have no effect on going concern audit opinion. The contribution of the results of this article will enrich research on going concern audit opinions during the pandemic.